Risk Appetite and Digital Financial Skills Toward Investment Intention: The Mediating Role of Financial Literacy - Nadia Amelia Pratiya Sari; Dewi Diah Fakhriyyah; Dwiyani Sudaryanti (LP2M IAIN Palopo, 2025)
The rapid advancement of digital technology has transformed financial behavior, particularly among Generation Z, who are increasingly exposed to investment opportunities through digital platforms. However, their readiness to invest is often constrained by limited financial literacy, leading to impulsive or poorly informed investment decisions. This study addresses the problem of how risk appetite and digital financial skills influence Generation Z’s investment intention, with financial literacy acting as a mediating variable. The objective of this research is to analyze both the direct and indirect effects of psychological and digital factors on investment intention within the framework of the Theory of Planned Behavior. A quantitative approach with a causal-comparative design was employed, using purposive sampling to collect primary data from 160 Generation Z respondents in Malang City through a structured Likert-scale questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0, which enabled the evaluation of measurement reliability, validity, and structural relationships. The results show that risk appetite, digital financial skills, and financial literacy each have a positive and significant effect on investment intention. Furthermore, financial literacy was found to significantly mediate the influence of both risk appetite and digital financial skills on investment intention. These findings highlight the critical role of financial literacy in transforming psychological willingness and digital competencies into informed investment behavior. The study contributes to the literature on financial behavior and provides practical insights for enhancing financial education strategies, particularly in strengthening sharia-based investment participation.